Вплив гідрометеорологічних умов на седиментаційні процеси - Насєдкін, Є.І.; Іванова, Г.М.; Клюшина, Г.В.; Довбиш, С.М. (Інститут геологічних наук НАН України, 2009)
В статье представлены результаты исследований влияния гидрометеорологических условий на характер и интенсивность седиментационных процессов в пределах полигона геоэкологического мониторинга (океанографическая платформа Экспериментального отделения Морского гидрофизического института НАН Украины, п.г.т. Кацивели). The results of scientific research of hydrometeorological conditions impact on nature and intensity of sedimentation processes are represented in the article. The research was conducted at the testing area of geoecological monitoring located on the oceanographic platform of the Experimental Department of Marine Hydrophysical Institute of NASU in Katsivali, Crimea, Ukraine.